Comparing the evolution of spatial inequality in China and India: a fifty-year perspective - Gajwani, Kiran; Kanbur, Ravi; Zhang, Xiaobo (International Food Policy Research Institute, 2006)
In the second half of the last century, both India and China have undergone major transitions and have moved to more liberalized economies. This paper relates the observed patterns in regional inequality to major events during this period. Because of China’s institutional barriers to migration, regional inequality is much higher than in India. Also, China’s decentralization and opening up are closely related to the observed regional inequality – particularly the inland-coastal disparity – since the reform period. From the Green Revolution age to the period of economic liberalization in India, the evolution of regional comparative advantage has shifted from the quality of land to the level of human capital as India integrates with the international market. Therefore, India’s states have become clustered into two clubs: more educated and less educated ones.